The impact of Education on the economic growth of developing countries: the case of Togo - Akwei, Kale (Graduate School of Business (GSB), 2021)
It is acknowledged in the literature that investment in human capital, more precisely education, has a positive impact on economic growth. However, studies have shown that this could not be proven in every country or region. As the 4th principle of the Sustainable Development Goals, education can be a contributing factor to development. This paper examines the impact of education on economic growth in Togo, a developing country, using time series data spanning from 1971 to 2018, which were sourced from the World Bank Database. It is set out to explore the existence of a relationship between education variables and economic growth proxied by the GDP per capita growth; the returns of investment in education; and the impact of the quality of education on growth. The study employed the ARDL ECM estimation method to examine the relationship between the variables used. Although the findings establish long-run co-integration among the variables, the long-run coefficients are statistically insignificant. However, it is evidenced that a change in the gross enrolment rate, mainly in primary education, and government expenditure in education, have a negative relation with GDP per capita growth. Key findings in the short-run estimation reveal that there is a positive and statistically significant relationship between enrolment in primary and secondary education, completion rate in secondary education, and GDP per capita. Notwithstanding the significance of the long-run estimates, the study recommends improved investment in education at all levels of education and a higher reliance on professional education that will quickly train students to enter the job market and perform revenue generating activities.